Evaluasi Pelaksanaan Supervisi Akademik di MTs Plus Sabilunnajah Bojonegoro - Pratiwi, Henny Indah; Windyaningsiwi, Ratih; Rusilowati, Ani; Astuti, Budi (Universitas Kristen Satya Wacana, 2023)
The teacher's role is very important in implementing the curriculum as well as in learning activities. Therefore, the activities carried out by the teacher need to be supervised or assisted so that the vision and mission of learning activities can be carried out properly. With the completion of academic supervision, it is hoped that there will be real support for teachers in developing their abilities to achieve curriculum goals. This study aims to evaluate supervision activities which consist of three stages, starting from planning academic supervision, implementing academic supervision, and following up on academic supervision. The case study in this research is at MTs Plus Sabilunnajah which is in Kanor District, Bojonegoro Regency, East Java. This research is a qualitative descriptive study with data collection techniques in the form of interviews, observation, and documentation. The results of the research at the planning stage have been carried out properly, the school principal carries out supervision planning by requesting the results of regular meetings. In the next stage, namely the implementation stage, the principal assesses every aspect of supervision starting from the suitability of the lesson plans with learning activities, learning processes, teacher performance, and classroom management by the teacher. From the results of the supervision implementation, it is known that there are some discrepancies between the RPP and the implementation of learning in the classroom. Another obstacle in the implementation of supervision is the schedule of supervision activities which are often delayed if the principal has an urgent need